Peran Lembaga Sertifikasi Profesi (LSP) Dalam Peningkatan Kualitas Sumber Daya Manusia pada Kejuruan Teknologi Informasi dan Komunikasi di BBPVP Kota Bandung - Fauzy, Sofya; Adji, Widwi Handari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the role of professional certification bodies (LSP) in improving the quality of human resource management in information and communication technology vocational schools at BBPVP Bandung. This research was conducted with quantitative methods. The study population was 110 people who were employees at the BBPVP Bandung City office. By using the slovin formula, the number of samples obtained from this pattern is 64 employees with a research confidence level of 90%. Data collection was carried out using a questionnaire. Testing or data analysis using SPSS V23. The analytical method used is validity test, reliability test, classical assumption test, and simple linear regression test. From all the tests carried out, the results obtained were that there was a role for LSP in improving the quality of human resources in information and communication technology vocational schools at BBPVP Bandung city. Keywords: professional certification institute, quality of human resource, information and communication technology